Development of a Complex Intervention to Support the Use of Sedative Drugs in Specialist Palliative Care (iSedPall) - Kauzner, Saskia; Schneider, Manuela; Heckel, Maria; Klein, Carsten; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Kolmhuber, Stefanie; Krauss, Sabine H.; Odierna, Beatrice; Rémi, Constanze; Schildmann, Jan; et al. (Palliative Medicine Reports, 2024)
Background: The option of intentional sedation to relieve intolerable suffering from treatment-refractory symptoms may elicit a feeling of safety for patients and informal caregivers as a last resort if the situation becomes unbearable. Many health care professionals feel uncomfortable and insecure in conducting intentional sedation due to specific challenges. We developed a complex intervention to support best practice use of sedative drugs in specialist palliative care in Germany based on previously published recommendations. This article aims at reporting the development of the intervention. Methods: The development of the intervention was based on theory and existing evidence with active stakeholder participation and patient and public involvement, following the updated Medical Research Council (MRC) Framework on complex interventions. A “Theory of Change,” drawing on expert-approved best practice recommendations and applying user-centered methods, fostered the development. The process encompassed study preparation, development of the elements of the intervention, and designing the multimodal intervention. For reporting, we adhere to the Guidance for Reporting Intervention Development framework. Results: The intervention is aimed at health care professionals working in specialist palliative care (inpatient and homecare settings) and consists of several components: (1) a screening tool, (2) the individual elements of the intervention, and (3) educational material for health care professionals to support them using the intervention. Additional information material was developed for patients and informal caregivers. Despite the benefits of stakeholder involvement, we faced some barriers due to limited health care staff and time resources and reservations regarding research in general. Discussion: A pilot study is planned for testing the overall feasibility of the intervention and exploring possible benefits for health care professionals to inform a subsequent fully powered implementation study. To deal with the challenges, we stayed in contact with the health care teams, maintained transparency, and provided opportunities for active participation.
CRIS-Team Scopus Importer:2025-02-04
Keywords: complex intervention; GUIDED; intervention development; palliative care; sedative drugs; theory of change

Documentation of Sedation in Palliative Care: A Scoping Review of Requirements, Recommendations, and Templates - Kauzner, Saskia; Heckel, Maria; Ostgathe, Christoph; Schneider, Manuela; Bausewein, Claudia; Schildmann, Eva; Kremling, Alexander; Ziegler, Kerstin; Klein, Carsten (Journal of Palliative Medicine, 2023)
Objective: To identify and describe requirements, recommendations, and templates for the documentation of sedation in adult palliative care.Introduction: International literature shows inconsistency in clinical practice regarding sedation in palliative care accompanied by legal, ethical, and medical uncertainties. Documentation in general serves as proof for previous treatments. In the context of intentional sedation to relieve suffering at the end of life, documentation provides a clear demarcation against practices of euthanasia.Inclusion Criteria: Articles with full-text version published in English or German since 2000, covering documentation requirements, recommendations, monitoring parameters or templates for sedation in adult palliative care were included.Methods: Scoping review following the JBI methodology. Search in online databases, websites of professional associations in palliative care, reference lists of relevant publications, the archive of the German "Journal of Palliative Medicine" and databases for unpublished literature were used. Search terms included "palliative care,' "sedation," and "documentation." The search was conducted from January 2022 to April 2022 with an initial hand search in November 2021. Data were screened and charted by one reviewer after conducting a pilot test of the criteria.Results: From the initial 390 articles (database search), 22 articles were included. In addition, 15 articles were integrated from the hand search. The results can be clustered in two sets of items, regarding either the documentation before or during sedation. The documentation requirements referred both to inpatient and homecare settings but in many cases, a clear assignment was missing.Conclusions: The guidelines analyzed in this study rarely cover setting-specific differences in documentation and often treat documentation as minor topic. Further research is needed addressing legal and ethical concerns of health care teams and, therefore, help to improve treatment of patients suffering from otherwise intractable burden at the end of life.
CRIS-Team WoS Importer:2023-05-26

Use of sedative drugs in specialist palliative care (iSedPall): a multi-modal intervention pilot study protocol - Ostgathe, Christoph; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Heckel, Maria; Kauzner, Saskia; Klein, Carsten; Krauss, Sabine H.; Kremling, Alexander; Schneider, Manuela; Seifert, Andreas; Ziegler, Kerstin; et al. (Pilot and Feasibility Studies, 2025)
Background: The use of sedative drugs in specialist palliative care is common but presents challenges due to specific medical, ethical, and legal considerations. There is little to no assistance for administering adequate sedative drug doses, ensuring accurate documentation before and during sedation, or managing ethically and legally challenging situations. In 2021, the SedPall study group published recommendations on the use of sedative drugs in palliative care. The German Association for Palliative Medicine endorsed the dissemination of the recommendations nationwide. However, disseminating recommendations alone does not necessarily lead to changes in clinical practice. In the project “Development and piloting of a multi-modal intervention for the use of sedative drugs in specialist palliative care (iSedPall)”, we will develop a multi-modal intervention that implements these national recommendations into practical tools for healthcare professionals in specialist inpatient and home care settings. In the pilot study described below, we aim to test the feasibility of the multi-modal intervention, its appropriateness, and acceptability as primary feasibility outcomes of the multi-modal intervention. Additionally, we aim to assess the feasibility of measuring healthcare professionals´ confidence in using sedative drugs as an outcome indicator for a possible subsequent study. Methods and analysis: We will use a mixed-methods approach to develop and pilot a multi-modal intervention. The primary feasibility outcomes and formative evaluation of the implementation process will be explored using quantitative (retrospective cohort study, survey) and qualitative elements (focus groups, interviews). Additionally, we will pilot the measurement of healthcare professionals´ confidence in using sedative drugs as an outcome indicator through a pre-post survey. Four specialist palliative care services will pilot the complex intervention for nine months. Due to the complexity of the intervention, we will follow the principles of the MRC framework for complex interventions and will apply a Theory of Change approach. The intervention will include different elements to be used throughout the patients’ treatment in inpatient and home specialist palliative care considering medical, ethical, and legal aspects for the use of sedative drugs and intentional sedation. The evaluation of the overall feasibility and the decision about proceeding to an implementation study will be based on the integration of quantitative and qualitative data, according to our mixed-methods approach. Discussion: This project is the first attempt to translate national recommendations on best practices for sedative drug use into a multi-modal intervention and tests its feasibility. The study group identified potential risks and challenges related to the intervention´s feasibility, acceptability, and appropriateness in advance. To mitigate these risks, the study protocol is based on a theoretical framework, developed through a Theory of Change approach. Participatory elements and the involvement of different stakeholders are expected to enhance user acceptance and feasibility, potentially improving the development of supporting materials for sedative drug use in specialist palliative care while considering the interests of non-professionals. Trial registration: Registered in the German Clinical Trials Register, DRKS-ID: DRKS00027241; Registered: 10/12/2021; https://www.drks.de/drks_web/setLocale_EN.do.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Multi-modal intervention; Palliative care; Sedative drugs; Study protocol